Two-dimensional Speckle Tracking Echocardiography and Three-dimensional Echocardiography Characterization of Left Atrial Giant Myxoma - Cacciapuoti, Fulvio (J Cardiovasc Echogr, 2016)
Myxomas are the most common cancerous nonneoplasms among the rare heart's tumors. Usually, they are located in the left atrium (LA). They are more frequent in women than in men and ranged in age from 30 to 50 years. Rarely, myxoma is completely asymptomatic and in that case represents a fortuitous discovery. However, usually, it is characterized by several symptoms as fatigue, dyspnea, chest pain, dizziness, cough, and sometimes, by sudden death. We refer on a case of LA myxoma found in a woman without symptoms but having a systolic precordial murmur. Two-dimensional echocardiography (2-DE) shown an unknown giant LA myxoma, almost completely occupying the atrial cavity. 2-D left atrial longitudinal speckle tracking echocardiography first allowed to note the changes in the percentage of “reservoir,” “conduit,” and “booster pump” phases of the left atrial function respect to normal subjects, revealing LA dysfunction. Three-dimensional echocardiography (3-DE) shown left atrial mass and its attachment to the atrial septum better than 2-DE. Furthermore, 3-DE allowed to define the shape of LA myxoma and its 3-D, irregular contour.